2009
DOI: 10.1182/blood-2008-12-195859
|View full text |Cite
|
Sign up to set email alerts
|

In utero transplantation of adult bone marrow decreases perinatal lethality and rescues the bone phenotype in the knockin murine model for classical, dominant osteogenesis imperfecta

Abstract: Autosomal dominant osteogenesis imperfecta (OI) caused by glycine substitutions in type I collagen is a paradigmatic disorder for stem cell therapy. Bone marrow transplantation in OI children has produced a low engraftment rate, but surprisingly encouraging symptomatic improvements. In utero transplantation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 52 publications
6
81
0
Order By: Relevance
“…44,45 The availability of Brtl mice will allow us to test such an approach for siRNA delivery by transducing Brtl mesenchymal stem cells with the lentiviral vector expressing the effective F-shRNA and transplanting them back to Brtl, as previously described. 20 Other novel tools may allow us to more safely manipulate mammalian cells than the use of lentivirus vectors. The identification in both human and mouse cells of specific and 'safe' loci for exogenous DNA integration, the AAVS1 and Rosa26, respectively, is particularly appealing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 The availability of Brtl mice will allow us to test such an approach for siRNA delivery by transducing Brtl mesenchymal stem cells with the lentiviral vector expressing the effective F-shRNA and transplanting them back to Brtl, as previously described. 20 Other novel tools may allow us to more safely manipulate mammalian cells than the use of lentivirus vectors. The identification in both human and mouse cells of specific and 'safe' loci for exogenous DNA integration, the AAVS1 and Rosa26, respectively, is particularly appealing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for clinically significant OI caused by structural defects in collagen, suppression of the Mut allele could in principle convert severe types III and IV to the minimally symptomatic OI type I, a situation particularly favorable to therapeutic strategies based on gene silencing. The promising preliminary data on stem cell transplantation in both murine models [18][19][20] and human OI 21,22 contributes to an appealing possibility for correcting the patient's own stem cells in vitro, and transplanting them back to the patient, after checking chromosomal rearrangements 23 or off-target effects 24 in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, whole bone marrow and bone marrow mesenchymal stem cells (MSC) have been transplanted in OI children with gains in body length and bone mineralization [8,9], while allogeneic fetal liver-derived stem cells transplanted in utero led to apparent phenotypic improvement in an OI fetus, although confounded by concomitant bisphosphonate use [10]. In rodent OI models, transplantation of whole bone marrow/bone marrow MSC led to increased collagen content [11], improved bone strength, reduced perinatal lethality [12], and increased osteoblast differentiation [13,14]. Marked therapeutic benefits were shown following transplantation of fetal MSC from human first trimester blood in a mouse model of human type III OI (oim) including improved bone plasticity and a two-third reduction in long bone fractures [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of mosaic carriers of OI-causing mutations [31,32] and bone marrow transplantation experiments in patients with OI and murine OI-models have shown that even a very small increase in cells producing normal collagen can have a striking effect on bone phenotype [27,33,34]. This clearly supports that the relative increase in normal collagen described above could have dramatic effects on bone health.…”
Section: Discussionmentioning
confidence: 74%
“…There are also concerns of high cumulative doses of bisphosphonates in patients treated from infancy. There are small-scale studies and case reports on stem cell transplantation, bone marrow transplantation and gene therapy in patients with OI and in mouse models with varying results [26][27][28][29][30] but to date no clinically available therapy has developed out of these publications. This study was aimed at investigating a novel genetic therapeutic approach for treating or limiting the severity of this disease.…”
Section: Discussionmentioning
confidence: 99%